2009
DOI: 10.1177/0021998308097730
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Zigzag Beam Theory for Composite and Sandwich Beams

Abstract: A new refined theory for laminated composite and sandwich beams that contains the kinematics of the Timoshenko Beam Theory as a proper baseline subset is presented. This variationally consistent theory is derived from the virtual work principle and employs a novel piecewise linear zigzag function that provides a more realistic representation of the deformation states of transverse-shear flexible beams than other similar theories. This new zigzag function is unique in that it vanishes at the top and bottom boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
198
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 19 publications
5
198
0
Order By: Relevance
“…The beam segment is defined in the ( , ) x z Cartesian system, where x is the beam longitudinal axis and z is the thickness coordinate. The superscript k denotes quantities within the th k layer with Using the same notation as for the RZT [18,19,21,23], we propose the following displacement field for the th k layer…”
Section: -1) Displacement Fieldmentioning
confidence: 99%
See 4 more Smart Citations
“…The beam segment is defined in the ( , ) x z Cartesian system, where x is the beam longitudinal axis and z is the thickness coordinate. The superscript k denotes quantities within the th k layer with Using the same notation as for the RZT [18,19,21,23], we propose the following displacement field for the th k layer…”
Section: -1) Displacement Fieldmentioning
confidence: 99%
“…Different works [18][19][20] have shown that beam models requiring 1 C continuity for the deflection field, such as that presented in Eq. (1), have theoretical difficulties to represent correctly the shear strain and the shear stress distributions in a clamped support where the following kinematic conditions are required…”
Section: Remarkmentioning
confidence: 99%
See 3 more Smart Citations